If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3(2k+6)-3k=-90
We move all terms to the left:
-3(2k+6)-3k-(-90)=0
We add all the numbers together, and all the variables
-3k-3(2k+6)+90=0
We multiply parentheses
-3k-6k-18+90=0
We add all the numbers together, and all the variables
-9k+72=0
We move all terms containing k to the left, all other terms to the right
-9k=-72
k=-72/-9
k=+8
| 69=5m-16 | | -3.5+2n=2 | | 2(x+2)+3x=2(x+7)+2 | | 14q–17=39 | | 7x+2-5x=22 | | 69=5m−16 | | 33=4x+2x+9 | | 7x+()=21 | | h-9=-12 | | 98=k+16 | | 3x-3+7x=37 | | -3(2x-1)=9x+3;x | | 9y+5=-51 | | w-56/4=9 | | -9+x+5x=3 | | 41.1=3.6(x+4.5) | | x.4x+3=23* | | 2.18k+38=-35 | | 3+7x+2x=111 | | (-12x+15)+3x=87 | | 4x+12-7x+28=37 | | 11-4(2x+3)=15 | | 92=x+6 | | 850=278+50p | | -3(r+8=-55 | | -10-x+3x=12 | | j4−1=2 | | 850=278+50m | | d−8.4=8.6 | | x-9=-80 | | 10=3x=8 | | e-45=-28 |